2005
DOI: 10.1074/jbc.m410384200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human VPS37C, a Component of Endosomal Sorting Complex Required for Transport-I Important for Viral Budding

Abstract: Endosomal sorting complex required for transport-I (ESCRT-I) is one of three defined protein complexes in the class E vacuolar protein sorting (VPS) pathway required for the sorting of ubiquitinated transmembrane proteins into internal vesicles of multivesicular bodies. In yeast, ESCRT-I is composed of three proteins, VSP23, VPS28, and VPS37, whereas in mammals only Tsg101(VPS23) and VPS28 were originally identified as ESCRT-I components. Using yeast two-hybrid screens, we identified one of a family of human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 37 publications
4
73
0
1
Order By: Relevance
“…The third band, of approximately 24 kDa, contained the Arabidopsis VPS28-1 homolog. These data are consistent with studies in mammals where VPS37 is known to interact with TSG101 (Bache et al, 2004;Eastman et al, 2005;Stuchell et al, 2004). The interaction between VPS37-1 4685 RESEARCH ARTICLE Role of VPS23 in plant cytokinesis Pull-down assays were performed using ubiquitin coupled to agarose and the ELC-HA protein was detected on the western blot using an anti-HA antibody.…”
Section: Elc Interacts With Components Of the Escrt I Complexsupporting
confidence: 73%
“…The third band, of approximately 24 kDa, contained the Arabidopsis VPS28-1 homolog. These data are consistent with studies in mammals where VPS37 is known to interact with TSG101 (Bache et al, 2004;Eastman et al, 2005;Stuchell et al, 2004). The interaction between VPS37-1 4685 RESEARCH ARTICLE Role of VPS23 in plant cytokinesis Pull-down assays were performed using ubiquitin coupled to agarose and the ELC-HA protein was detected on the western blot using an anti-HA antibody.…”
Section: Elc Interacts With Components Of the Escrt I Complexsupporting
confidence: 73%
“…This shared protein motif and the low level of sequence identity were not significant enough to identify the VPS37 homologs in human, Drosophila, C. elegans and plants. However, recent experimental interaction studies have identified the four human orthologs of VPS37 (see Supplementary material Table S2 and Figure S2C) [40,43]. Using the human VPS37 sequences, we identified putative homologs in Drosophila and C. elegans and two putative Arabidopsis and rice homologs (see Supplementary material Table S2 and Figure S2C).…”
Section: Escrt-imentioning
confidence: 99%
“…Therefore, VPS23 does not function as an ubiquitin conjugating enzyme and yet it is still able to bind ubiquitinated proteins. Via its C-terminal coiled coil structure, the human VPS23 homolog TSG101 interacts with VPS27, VPS28 [40] and VPS37 [41]. In rice and Arabidopsis, one and two putative VPS23 homologs are present, respectively (see Supplementary material Table S2 and Figure S2A).…”
Section: Escrt-imentioning
confidence: 99%
“…HIV-1 Gag was previously reported to colocalize with Tsg101 on endosomes (Eastman et al, 2005) (also see Fig. 4, A-A").…”
Section: Competition Of Hiv-1 Gag With Tom1l1 For Interaction With Tsmentioning
confidence: 99%